Intraoperative Cardiac Complications in Liver Transplantation: Preoperative Evaluation – A Narrative Review - Nedim Çekmen; Ahmed Uslu (Indian Journal of Transplantation)
The decisive treatment for end-stage liver disease (ESLD) is liver transplantation (LT). Perioperative management of LT is one of the most challenging issues for anesthesiologists. The heart and liver are organs that are closely related to both health and disease. Cardiac actions are the most essential cause of mortality during LT and have a significant impact on overall outcomes. The pathophysiological effects of ESLD on the circulatory system cause critical difficulties in perioperative treatment. In order to perform correct anesthesia management in LT, it is crucial to understand and know the multiplex pathogenesis of ESLD and the changes in the afflicted systems, especially the heart. LT is a dynamic process and one of the most stressful cardiovascular events an ESLD patient can experience. Anesthesia management of LT is a highly complex procedure requiring an exact multidisciplinary team attitude. A comprehensive cardiovascular system (CVS) assessment, planning, coordination, collaboration, and optimization with a multidisciplinary team in the preoperative period is essential for the management and treatment of possible intraoperative cardiac complications (ICCs). In light of the literature, our review focuses on the value and importance of detailed preoperative CVS evaluation in anesthesia management in preventing significant ICCs that may occur in the intraoperative period in LT patients.